Pengaruh Peringkat Obligasi, ROA, DER, FIRM SIZE Terhadap Yield Obligasi - Meliyanti; Ferikawita Sembiring (JRB-Jurnal Riset Bisnis, 2021)
This study aims to determine the effect of bond ratings, return on assets (ROA), debt to equity ratio (DER), and firm size on yield to maturity (YTM) on several corporate bonds on the Indonesia Stock Exchange during the 2013-2018.The research method used is a quantitative research approach. The research method used was purposive sampling which resulted in 71 bonds from 29 firms as the samples. The results showed that bond ratings and DER had a negative effect on bond yields, while ROA and company size had no effect. This finding supports the findings of several previous studies which simultaneously strengthen the position of bond ratings and DER as determinants of yield. The results of the classical assumption test show that the model formed is free from classical problems so that it can be a good predictor of bond yields.